Framing Media Online Atas Pemberitaan Isu Politik Uang dalam Pilkada Serentak 2018 - Lestari Nurhajati; Xenia Angelica Wijayanto (Jurnal Adhyasta Pemilu, 2018)
Money politics is one of the issues that has always been a problem in the process of electing Regional Heads (Pilkada), including in the Pilkada on June 27, 2018. All parties involved in the election process, both voters, Election Management Bodies (KPU) and Bawaslu, always see that the case of money politics is a problem that seems never resolved, and recurs from year to year. Moreover, the mass media, including online media always discuss the issue of money politics in Pilkada activities in Indonesia. This study aims to find out how the online media in Indonesia conducts framing news in the issue of money politics, especially in the 2018 Simultaneous Regional Election. Framing theory in media reporting becomes interesting to study because this theory sees that the issue by media perspective in reporting becomes important value for the media readers. Media audiences can be directly and indirectly affected by various news framing by the media. Qualitative methods with Entman’s framing approach are used to analyze framing in 5 online media with the most access in Indonesia, they are: Tribunnews.com, Detik.com, Liputan6.com, Kompas.com, and Sindonews. com. The results of this study indicate that in general the media has framing that is not much different. It’s just in the parts of treatment recommendation it appears that the media does not explicitly show their alignment with regulations and ethics which is clearly prohibit the practice of money politics in the elections.